Too big to fail : the inside story of how Wall Street and Washington fought to save the financial system--and themselves - Sorkin, Andrew Ross (New York : Penguin Books, 2010)
Presents a moment-by-moment account of the recent financial collapse that documents state efforts to prevent an economic disaster, offering insight into the pivotal consequences of decisions made throughout the past decade
Originally published: New York : Viking, 2009. With a new afterword
Keywords: Global Financial Crisis, 2008-2009; Financial crises -- United States -- History -- 21st century; Financial crises -- United States -- History